Individual and social variables and their effect on Case/Care Manager Job Satisfaction: an exploratory study - Cosentino, Chiara; Bettuzzi, Morena; Campioli, Giulia; Di Marco, Valeria; Giacopuzzi, Giulia; Marinoni, Ivana; Orlandini, Lorenzo; Palermo, Angelo; Pattacini, Siria; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2017)
Background and aims: The Case/Care Manager (CCM) is a new position for in the Italian National Health Service scenario. Job satisfaction plays a key role for the CCM to engage in his work, accomplishing it in a complete. Nurses’ job satisfaction is a complex construct and many different variables can influence it: personal characteristics, cultural characteristic, social characteristic, organizational characteristic, and environmental characteristic. The main aim of this study is to assess the job satisfaction in a sample of CCM and to assess if and how Social Variables (organizational climate and health) and Individual (socio-demographic variables, coping strategies, emotion regulation) relate to the CCM job satisfaction. Methods: This study has a quantitative exploratory cross-sectional design. Participants were Nurse CCM with or without specific training who filled a battery of questionnaires : Job Satisfaction Survey (JSS) , section three of ICONAS questionnaire, section five of the Multidimensional Organizational Health Questionnaire (MOHQ), anamnestic sheet, Coping Orientation to the Problems Experienced (COPE-NVI-25), and Emotion Regulation Questionnaire (ERQ). The battery was administered online on the website of Italian Case Manager, Italian Association of Care Manager, and IPASVI Colleges. It was also distributed during the National Congress for Case Manager in Padua. Results: 103 participants took part in the study. The total mean score of JSS was 117,28 (S.D.=21,12). The emotional regulation strategy most used was the “Cognitive Response”, and the most used Coping strategy was “Problem Oriented”. There were significant correlations between JSS and Social variables in the total score (ICONAS r=.574 p<0.01; MOHQ (positive indicators) r=.608 p<0.01; MOHQ (negative indicators) r=-.634 p <0.01) and in its subscales. There were also significant correlations between JSS subscales and Individual variables (COPE and ERQ). Participants with a specific training tend to use the emotion regulation strategy “Negative interpretation self-oriented” (U 910.500 p<0.005) and “Distraction” (U 885.000 p<0.005) more than those without specific training. The same significant difference was found in JSS pay (t=-2,48 per p<0.05) and JSS Fringe Benefits (t=-2,07 per p<0.05). Discussion: The CCM job satisfaction seems to be ambivalent. It seems to be not entirely polarized on presence/absence, but rather still in a gray area. organizational climate and health influence significantly the overall perception of job satisfaction and its different areas. The most “avoiding” emotional regulation strategies, seem to negatively affect the perception of satisfaction. Emotional regulation and coping strategies related to challenges focusing and management, along with the individual perception of collaboration, positively influence satisfaction. Participants who underwent a specific CCM training, committing themselves financially and personally, perceive less job satisfaction when their role is not recognized in terms of pay. This study showed that that the main strategies used to regulate emotions are the Cognitive Response and the Social Contact. We suggest that further studies could be made to define the links between individual strategies and the presence of chronic distress and we suggest that a specific training on coping and emotion regulation may be implemented in graduation and post-graduation courses